Sustainable tourism in the Alpen-Adria region - Gosar, Anton (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2003)
In this paper we would like to focus on the awareness of sustainable management of resources among hotel managers and tourists visiting the mountainous parts of the Alpen- Adria region (Southeastern Alps, Northern Adriatic) of Europe. We are going to elaborate on results of quantitative questionnaires made in several tourist resort of the region. Our study proves that the environment has become the problem of the society and the economy where tourism is taking place.
Keywords: Austria; Avstrija; ecology; ekologija; environmental protection; Italija; Italy; Slovenia; Slovenija; sonaravni razvoj; sustainable development; tourism; trajnostni razvoj; turistična geografija; turizem; varstvo okolja